2013
DOI: 10.1111/ap.12006
|View full text |Cite
|
Sign up to set email alerts
|

Treating Youth Depression and Anxiety: A Randomised Controlled Trial Examining the Efficacy of Computerised versus Face‐to‐face Cognitive Behaviour Therapy

Abstract: Barriers to accessing psychologists for the treatment of depression and anxiety include a shortage of specialised therapists, long waiting lists, and the affordability of therapy. This study examined the efficacy of a computerised-based self-help program (MoodGYM) delivered in-conjunction with face-to-face cognitive behavioural therapy (CBT) to expand the delivery avenues of psychological treatment for young adults (aged 18-25 years). Eighty-nine participants suffering from depression and/or generalised anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 49 publications
(49 reference statements)
1
51
0
3
Order By: Relevance
“…Four studies evaluated DHIs targeting both anxiety and depression: three evaluated a cCBT intervention (Melnyk et al., ; Sethi, ; Wong, Kady, Mewton, Sunderland, & Andrews, ); the other evaluated a multitheoretical intervention incorporating motivational‐enhancement, cognitive behavioural strategies and behavioural principles (Ruggiero et al., ). A total of 2,173 participants were recruited to these trials; age range 12–25 years, ( M = 17.9, Mdn = 18.5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies evaluated DHIs targeting both anxiety and depression: three evaluated a cCBT intervention (Melnyk et al., ; Sethi, ; Wong, Kady, Mewton, Sunderland, & Andrews, ); the other evaluated a multitheoretical intervention incorporating motivational‐enhancement, cognitive behavioural strategies and behavioural principles (Ruggiero et al., ). A total of 2,173 participants were recruited to these trials; age range 12–25 years, ( M = 17.9, Mdn = 18.5).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2,173 participants were recruited to these trials; age range 12–25 years, ( M = 17.9, Mdn = 18.5). Participants were recruited with mild‐to‐moderate anxiety symptoms and/or depression symptoms (Sethi, ), or because they lived in an area which had experienced a significant natural disaster (Ruggiero et al., ). Participants completed the intervention in school (Wong et al., ), or in a community centre or on university campus (Sethi, ).…”
Section: Resultsmentioning
confidence: 99%
“…Three programs were for depression: The Journey (Stasiak, Hatcher, Frampton, & Merry, 2014), SPARX (Fleming, Dixon, Frampton, & Merry, 2012;Merry et al, 2012) and Mood Helper (Clarke et al, 2009) and were conducted in populations at high risk of (Clarke et al, 2009;Fleming et al, 2012;Merry et al, 2012) or diagnosed with (Stasiak et al, 2014) depression. Two programs were for both anxiety disorders and depression: MoodGym (Calear, Christensen, Mackinnon, Griffiths, & O'Kearney, 2009;Ellis, Campbell, Sethi, & O'Dea, 2011;Sethi, 2013;Sethi, Campbell, & Ellis, 2010) and Think Feel Do (Stallard, Richardson, Velleman, & Attwood, 2011) and were conducted in a general population of young people (Calear et al, 2009) or populations at risk of depression or an anxiety disorder (Ellis et al, 2011;Sethi, 2013;Sethi et al, 2010). One program was specifically for young adults with a diagnosis of social anxiety disorder (unnamed) (Tillfors et al, 2011).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the studies of cCBT for depression in young people, all were considered to have low therapist input (Clarke et al, 2009;Fleming et al, 2012;Stasiak et al, 2014). For cCBT for both anxiety and depression in young people, in the general population study (Calear et al, 2009), there was low therapist input, but all studies in populations at risk of anxiety and depression were considered to have some therapist input (Ellis et al, 2011;Sethi, 2013;Sethi et al, 2010;Stallard et al, 2011).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Empirical research supports this theory by having shown both the efficacy of CBT protocols in treating mood, anxiety, and eating disorders and the psychopathological role played by cognitive beliefs and processes in emotional disorders (Burns et al, 2013;Haaga, Dyck, & Ernst, 1991;Sethi, 2013;Spielmans et al,, 2013). However, proponents of CBT are in danger of taking for granted that in CBT the therapeutic process only depends on specific cognitive interventions that improve rational, reality-checking thinking (Leahy, 2012).…”
mentioning
confidence: 97%